2020
DOI: 10.9789/2175-5361.rpcfo.v12.7069
|View full text |Cite
|
Sign up to set email alerts
|

Hansen’s disease patients’ perceptions on their altered fundamental human needs: indications for self-care

Abstract: Objetivo: Analisar a percepção de pacientes com hanseníase sobre suas necessidades humanas básicas (NHB) alteradas. Método: Pesquisa qualitativa e descritiva, realizada com dez pacientes inscritos no Programa Nacional de Controle da Hanseníase (PNCH) em uma Unidade Básica de Saúde (UBS) em Belém-PA. Dados coletados de agosto a setembro de 2017, por meio de entrevista semiestruturadas e prontuários dos participantes. Os dados foram organizados e analisados na perspectiva da análise de conteúdo. A pesquisa foi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 35 publications
0
18
0
6
Order By: Relevance
“…The most frequently absent detail in the included studies was the information on the influence of the researcher on the research (question 7, S5 Appendix); only five studies reported this item. [34,45,58,62,73] Seventeen studies [12,19,43,44,47,59,63,65,[69][70][71][75][76][77]79,80,83] had no obvious statement locating the researcher culturally or theoretically.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently absent detail in the included studies was the information on the influence of the researcher on the research (question 7, S5 Appendix); only five studies reported this item. [34,45,58,62,73] Seventeen studies [12,19,43,44,47,59,63,65,[69][70][71][75][76][77]79,80,83] had no obvious statement locating the researcher culturally or theoretically.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…This synthesised finding consisted of three categories and 43 findings from 27 studies. [12,16,18,[43][44][45][48][49][50]52,54,[58][59][60][62][63][64][65][66][67]72,76,78,[81][82][83]87] This synthesis documented the effects of leprosy on the skin, eyes, wounds on their limbs, nerve injury, and pain. Due to poor access to healthcare and delays in treatment, the individuals suffering from leprosy developed deformities that impacted their day-to-day activities.…”
Section: India and Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…A hanseníase, por se tratar de uma doença socialmente estigmatizada, carrega em si aspectos emocionais bastante relevantes como o medo, a desesperança e o descontentamento. Com o surgimento das alterações corporais, a qualidade de vida destas pessoas é atingida negativamente pelo fato da sociedade impor um padrão estético voltado para a beleza e integridade física (FORTUNATO et al, 2019;LANA et al, 2014;NEIVA;GRISOTTI, 2019;PALMEIRA, 2020;SILVA et al, 2014).…”
Section: Estigmas Relacionados à Imagem Corporalunclassified
“…Com isso, evidencia-se que, devido ao estigma advindo de crenças religiosas perpetuado na sociedade até dias atuais, o diagnóstico e tratamento da hanseníase vem acompanhado de preconceitos, julgamentos e sentimentos de tristeza, inconformidade, não aceitação, indignação e até mesmo desconhecimento acerca de como a infecção, de fato, desenvolve-se (PALMEIRA; QUEIROZ; FERREIRA, 2013; SILVA, 2017). Por fim, um fator de grande relevância diante dos estudos é a questão da omissão do diagnóstico, que funciona como autoproteção contra atitudes discriminatórias, tais como a exclusão social, o preconceito e a estigmatização (BEZERRA et al, 2011;GONÇALVES et al, 2018;LUSTOSA et al, 2011;NEIVA;GRISOTTI, 2019;NUNES;OLIVEIRA;VIEIRA, 2011;PALMEIRA et al, 2020).…”
unclassified